PEMODELAN DAN OPTIMASI PRODUKSI FLAVORING AGENT MENGGUNAKAN OPTSYS - Eneng Tita Tosida (KOMPUTASI, 2006)
Flavoring agent is an important substance in foods industrial, beverage, cosmetics, pharmacy, and woof, in deed the uses of this more expansion to fragrance and air freshener. The research (Tri-Pnji et al., 1992)show that using by cocoa sweetening bioconversion, as a grow medium for Trichoderma harzianum, can be produced flavoring agent as well as a complex compound. The flavoring agent production as a result this research needs to be optimized. So that, it is necessary to research about optimization bioconversion system, which is included ph, mixing speed, and fermentation time  management. The research objective is building flavoring agents bioconversion model systems, which is focused to batch system, and to be continued by simulation and optimization system. This system implemented using simulator software GPSS Fortran and OPTSYS(Optimization System), pass through thr Comby Strategy